Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 130844 by mnjuly1970 last updated on 29/Jan/21

                 ...   advanced   calculus...      prove  that::      ∫_0 ^( (π/3)) (dx/( ((cos^2 (x)))^(1/3) )) =((2^(1/3) (√π))/( (√3)))

...advancedcalculus...provethat::0π3dxcos2(x)3=213π3

Answered by Dwaipayan Shikari last updated on 29/Jan/21

∫_0 ^(π/3) (cosx)^(−(2/3)) dx=−∫_1 ^(1/2) t^(−(2/3)) (1−t^2 )^(−(1/2)) dt  =∫_0 ^1 t^(−(2/3)) (1−t^2 )^(−(1/2)) dt−∫_0 ^(1/2) t^(−(5/6)) (1−t^2 )^(−(1/2)) dt  =(1/2)∫_0 ^1 u^(−(5/6)) (1−u)^(−(1/2)) du−(1/2)∫_0 ^(1/( (√2))) u^(−(5/6)) (1−u)^(−(1/2)) du  =((Γ((( 1)/6))Γ((1/2)))/(2Γ((2/3))))−(1/2)Σ_(n=0) ^∞ ((((1/2))_n )/(n!))∫_0 ^(1/( (√2))) u^(n−(5/6)) du  =((Γ((5/6))(√π))/(2Γ((2/3))))−(3/( (2)^(1/3) )) _2 F_1 ((1/6),(1/2),(7/6),(1/4))

0π3(cosx)23dx=112t23(1t2)12dt=01t23(1t2)12dt012t56(1t2)12dt=1201u56(1u)12du12012u56(1u)12du=Γ(16)Γ(12)2Γ(23)12n=0(12)nn!012un56du=Γ(56)π2Γ(23)3232F1(16,12,76,14)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com